Emotion-focused therapy as a transdiagnostic treatment for depression, anxiety and related disorders: Protocol for an initial feasibility randomised control trial - Timulak, Ladislav; Keogh, Daragh (My University, 2020)
Background: Depression, anxiety and related disorders, including obsessive-compulsive disorders and trauma/stressor related disorders, have high prevalence, chronic courses and cause significant impairment. These disorders are also highly co-morbid, and appear to share etiology and maintenance factors. Recent developments have seen the emergence of transdiagnostic approaches that systematically address the common/shared features of these disorders. A key advantage of transdiagnostic approaches is that they can reduce the pressure on mental health professionals to be proficient in a plethora of single-disorder focused treatments. Currently almost all transdiagnostic approaches come from cognitive-behavioural therapy (CBT). However, not all clients prefer or benefit from CBT. Emotion-focused therapy (EFT) represents an evidence-based alternative to CBT. This study aims to examine a transdiagnostic adaptation of EFT (EFT-T) as a treatment for depression, anxiety and related disorders. Method: The current study is a randomised controlled trial that aims to establish the efficacy of EFT-T vs. wait-list control in the treatment of depression, anxiety and related disorders. Up to 40 clients presenting in a psychology/counselling service will be randomly assigned to two conditions: EFT-T (n=20) and wait-list control, with delayed intervention (n=20). Primary outcome measures will be the Overall Anxiety Severity and Impairment Symptoms, the Overall Depression Severity and Impairment Symptoms, and the Clinical Outcome in Routine Evaluation – Outcome Measure. Disorder specific self-report measures will also be used to assess the main symptomatology of respective primary diagnoses. Clients will be assessed prior to therapy, at week 16, at end of therapy, and at 6 months follow-up. Discussion: This study aims to provide an initial test of EFT-T as a transdiagnostic treatment for depression, anxiety and related disorders. It will provide estimates of effects sizes that can inform power calculations for a comparative trial, comparing EFT-T to a standard transdiagnostic treatment, CBT. Registration: ISRCTN11430110; registered on 07 January 2019.
PUBLISHED
Keywords: Emotion-focused therapy; Transdiagnostic; EFT-T; Depression; Anxiety; Protocol